Presumptive migrating gall bladder mucocoele in two dogs with gall bladder rupture. (13th December 2017) - Burchell, R. K.; Thornton, L.; Lim, C. K.; Murakami, M.; Nakamura, Y.; Gal, A.
Abstract : A 10‐year‐old neutered female soft‐coated wheaten terrier and a 10‐year‐old, entire female Pomeranian were presented for vomiting and anorexia. Using ultrasound, an oval structure with a stellate, kiwifruit‐like appearance typical of a gall bladder mucocoele was observed in the caudal abdomen of the soft‐coated wheaten terrier and adjacent to the liver in the Pomeranian. There was also a moderate volume of abdominal effusion in both dogs. Cytology of the peritoneal fluid indicated a sterile exudative process but varied between the two dogs, with an absence of bile pigment in the soft‐coated wheaten terrier and marked bile peritonitis in the Pomeranian. An entire free‐floating ectopic mucocoele was confirmed via exploratory laparotomy with concomitant gall bladder rupture and common bile duct obstruction. Both dogs recovered completely after surgery. This is the first report of cases of gall bladder rupture with entire free‐floating gall bladder mucocoeles in dogs.